Exome sequencing and electro-clinical features in pediatric patients with very early-onset retinal dystrophies: A cohort study. (March 2021) - Suppiej, A.; Ceccato, C.; Maritan, V.; Cermakova, I.; Colavito, D.; Leon, A.
Abstract: Background and objective: Inherited retinal dystrophies (IRDs) are a major cause of childhood blindness. Timely diagnosis requires a high level of clinical suspicion from both neurologists and ophthalmologists and is increasingly important given recent advancements in gene therapy. We focused our study on genotype-phenotype associations in very early-onset forms of retinal dystrophy, the least well characterized and most challenging diagnostic subgroup. Methods: From January 12, 2015 to March 31, 2017, we prospectively performed whole exome sequencing targeted on the phenotype of non-syndromic IRDs and phenotype characterization in a cohort of 68 children affected by very early-onset inherited retinal dystrophies, defined by the onset before five years of age. Phenotype parameters included age at onset, clinical presentation, ophthalmic evaluation, electrophysiological patterns and clinical course. Results: A genetically confirmed diagnosis was achieved in 50 out of 60 (83%) families. The median age at onset was 4 months (<6 m in 70%, < 2 y in 82% of the cases). Clinical presentation was associated with visual loss and nystagmus in the majority of patients. Three (CNGB3, CNGA3 and CACNA1F) out of 22 genes considered pathogenic in the cohort, accounted for 51% of all IRD's, all within the class of stationary IRDs. Conclusions: This study reports on the largest cohort of very early-onset retinal dystrophies, including a description of electroretinography patterns. The electro-clinical phenotype coupled with genetic diagnosis provided additional clues for child neurologists dealing with low vision and nystagmus in infancy. A high level of clinical suspicion improves the diagnosis with important implications for the future of the affected child. Highlights: Diagnosis of low vision in infancy bridges and challenges paediatric neurology and ophthalmology. Inherited retinal dystrophies are major causes of inherited childhood blindness. Very early onset forms of retinal dystrophy are the least well characterized and most difficult diagnostic subgroup. Exome analysis performed in clinically focused tiered fashion allowed a detection rate of 82%, the highest reported to date. We propose an electro-clinical diagnostic algorithm for low vision and nystagmus in infancy.